Development model history learning based on character in student students in the city of Padangsidimpuan - Burhanuddin Burhanuddin; Azwar Ananda; Jalius Jama; Maria Montesori (International Conferences on Educational, Social Sciences and Technology)
The objectives of this research are (1) To describe the development of character-based history learning to focus on exemplary on religious components, honest and homeland love for high school students in Kota Padangsidimpuan, (2) to design the development of character-based history learning on religious components, honest and homeland love for high school students covering Knowing the validity, effectiveness and practicality of the development of character-based history learning for high school students in accordance with the values of religious character, honest and love the homeland. Research design is Research and Development using ADDIE model. This research was conducted by SMA Negeri Padang Sidimpuan. The subject of product trial involves 30 students by implementing pretest-postest through the result of questionnaire of character-based history learning Data collecting technique in the form of questionnaire, interview, observation and test. Data analysis technique description. The results of research illustrate that the character-based history learning model such as religious character, honest, tolerance, democratic, spirit of nationality, love the homeland, love peace with teaching materials in the form of validated model books validation, practicality and effectiveness.